Electrochemical Behavior of Aromatic Compounds on Nanoporous Gold Electrode - Bui Thi Phuong Quynh; Byun, Ji Young; Kim, Sang Hoon (ELECTROCHEMICAL SOC INC, 2018)
This study aimed at investigating the electrochemical behavior of benzene and its substituted derivatives on nanoporous gold and assessing the possibility of utilizing this electrode as a platform for simultaneous detection of different aromatic compounds. Cyclic voltammetric studies were performed with benzene, hydroquinone, catechol, phenol, 2-aminophenol, 2-chlorophenol as well as their mixtures on the nanoporous gold prepared from dealloying of AuxSi1-x films. The nanoporous structure was found to provide enhanced electro-oxidation of hydroquinone, catechol, phenol, 2-aminophenol and 2-chlorophenol and remarkable fouling resistance in the electro-oxidation of phenol and 2-aminophenol compared to the compact and flat gold electrode. Interestingly, oxidation potentials of these aromatics appear to be affected significantly by the attachment of functional groups to the benzene ring. Based on the onset oxidation potentials, the easiness of oxidation at nanoporous gold was found to follow the order: hydroquinone > catechol > 2-aminophenol > 2-chlorophenol, phenol > benzene. Moreover, nanoporous gold was found to be advantageous over nanoporous platinum for potential application in simultaneous analysis employing voltammetric techniques as it could offer discernable peak potential separation in the electro-oxidation of the different aromatics. (C) 2018 The Electrochemical Society.
Keywords: DOPED DIAMOND ANODES; PLATINUM THIN-FILMS; CYCLIC VOLTAMMETRY; CARBON ELECTRODE; HIGH SELECTIVITY; AQUEOUS-MEDIA; OXIDATION; HYDROQUINONE; CATECHOL; PHENOL